Method for preparing nano-silver or composite nano-silver based on oak leaf extracting solution and application

By mixing the oak leaf extract with silver salt or composite silver salt solution under ultrasonic conditions for reduction reaction, stable nanosilver or composite nanosilver is prepared, which solves the problem of using toxic chemical reducing agents in the prior art, and achieves efficient and environmentally friendly nanosilver preparation, with a wide range of antibacterial, antiviral and wound healing applications.

CN119910190APending Publication Date: 2025-05-02DALIAN COMINE NANO TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510004654.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, toxic chemical reducing agents are often used when preparing nanosilver, which leads to contamination and toxic side effects, and the preparation process is complex and the cost is high.

Method used

The reduction reaction of oak leaf extract and silver salt or composite silver salt solution under ultrasonic conditions was performed to prepare stable nanosilver or composite nanosilver solution and gel, avoiding the use of toxic chemical reducing agents.

Benefits of technology

It has achieved the preparation of nano silver or composite nano silver with smaller particles, which has multiple effects of efficient antibacterial, antiviral and promoting wound healing. It has simple technology, less equipment investment, low cost, and environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910190A_ABST
    Figure CN119910190A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing nano-silver or composite nano-silver based on an oak leaf extracting solution and application, and belongs to the technical field of medical materials. The preparation method comprises the following steps: mixing an oak leaf extracting solution with a silver salt solution or a composite solution of silver salt, copper salt and zinc salt in a volume ratio of (1000: 1)-(100: 5), and carrying out reduction reaction under the ultrasonic action to prepare a stable nano-silver solution or a composite nano-silver solution; the concentration of silver ions in the silver salt solution is 50-1000 [mu] g / ml; in the composite solution of the silver salt, the copper salt and the zinc salt, the concentration of silver ions is 50-1000 mu g / ml, the concentration of copper ions is 25-500 mu g / ml, and the concentration of zinc ions is 25-500 mu g / ml. The preparation process is simple, the equipment investment is small, the cost is low, a large number of nano-silver particles can be prepared within a short time, the preparation process is free of pollution and does not contain any harmful chemical component, and nano-silver prepared from the oak leaf extracting solution is a green and environment-friendly product, has efficient and broad-spectrum antibacterial and antiviral characteristics and is suitable for industrial production. Wide application prospects are realized in the field of medical materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and specifically relates to a method for preparing nanosilver or composite nanosilver based on oak leaf extract and application thereof. Background Art

[0002] Silver nanoparticles are single silver particles with a particle size between 1 and 100 nanometers. They are known as the new generation of antibacterial and antiviral agents in the 21st century. Silver nanoparticles have broad-spectrum and highly effective antibacterial and antiviral properties, and their effects are long-lasting and not prone to drug resistance. Silver nanoparticles have been widely used in various medical materials, such as wound dressings, antibacterial gels, surgical masks, medical catheters, medical surgical instruments, and implants in human tissues. Silver nanoparticles have a wide range of market demands in the fields of pharmaceutical materials, medical and health care, daily necessities, building materials, and the electronics industry.

[0003] The main methods for preparing nanosilver include physical reduction, chemical reduction, and plant reduction. The physical reduction method is relatively simple, but it has high requirements for equipment, high energy consumption, and high cost. The chemical reduction method is more common, but the reducing agents and stabilizers used are mostly toxic reagents, which pollute the environment. At the same time, the reaction conditions need to be strictly controlled, and the preparation technology requirements are high. The plant reduction method is a green method for preparing nanosilver, especially the use of plant extracts with pharmaceutical value to prepare nanosilver. It is green and environmentally friendly, and can make nanosilver have multiple functions such as antibacterial, anti-inflammatory, and promoting wound healing.

[0004] Oak (Querus mongolica Fisch) is a deciduous tree of the genus Quercus in the Fagaceae family, including Mongolian oak, Liaodong oak, Aconite oak, and Quercus serrata. Oak leaves are also a traditional Chinese medicine with the effects of clearing away heat and relieving diarrhea, relieving cough, detoxifying and reducing swelling. They can be used to treat dysentery, enteritis, indigestion, bronchial salts, carbuncle and hemorrhoids. However, so far, there has been no report on the preparation of nanosilver using oak leaf extract as raw material and related experimental research. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for preparing nanosilver or composite nanosilver based on oak leaf extract and its application. The present invention uses oak leaf extract in combination with ultrasonic technology to prepare nanosilver solution, composite nanosilver solution, nanosilver gel or composite nanosilver gel. The use of oak leaf extract can avoid the toxic and side effects caused by the use of chemical reducing agents such as hydrazine hydrate and sodium borohydride to prepare nanosilver. The present invention can prepare nanosilver or composite nanosilver with smaller and more stable particles. The prepared nanosilver solution, composite nanosilver solution, nanosilver gel or composite nanosilver gel has very good application value in promoting wound healing in human and animal antibacterial and antiviral treatments.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing nanosilver or composite nanosilver based on an oak leaf extract, comprising the following steps: mixing the oak leaf extract with a silver salt solution or a composite solution of silver salt, copper salt, and zinc salt, and performing a reduction reaction under ultrasonic action to prepare a stable nanosilver solution or a composite nanosilver solution.

[0008] Based on the above technical solution, further, the volume ratio of the oak leaf extract to the silver salt solution or the composite solution of silver salt, copper salt and zinc salt is 1000:1 to 100:5; and the reduction reaction time is 10 to 60 minutes.

[0009] Based on the above technical scheme, further, the silver ion concentration in the silver salt solution is 50-1000 μg / ml; the silver ion concentration in the composite solution of silver salt, copper salt and zinc salt is 50-1000 μg / ml, the copper ion concentration is 25-500 μg / ml, and the zinc ion concentration is 25-500 μg / ml.

[0010] Based on the above technical scheme, further, the silver ion concentration in the silver salt solution is 50-200 μg / ml; the silver ion concentration in the composite solution of silver salt, copper salt and zinc salt is 50-200 μg / ml, the copper ion concentration is 25-100 μg / ml, and the zinc ion concentration is 25-100 μg / ml.

[0011] Based on the above technical solution, further, the silver salt is silver acetate, the copper salt is copper acetate, and the zinc salt is zinc acetate.

[0012] Based on the above technical solution, further, the ultrasonic conditions are as follows: ultrasonic frequency 25-80KHz, ultrasonic power 54-1080W.

[0013] Based on the above technical scheme, further, the preparation process of the oak leaf extract is: crush the dried oak leaves, add purified water to the obtained oak leaf dry powder to form a 0.1wt% to 5wt% solution, extract at 80 to 100°C for 15 to 60 minutes, then place at 1 to 4°C for 10 to 24 hours, filter, centrifuge, take the supernatant, and filter and sterilize it with a filter membrane.

[0014] Based on the above technical solution, further, the content of oak leaf dry powder in the solution is 0.5wt% to 2wt%.

[0015] Based on the above technical solution, further, the centrifugal conditions are: the rotation speed is 2000-5000 rpm, and the centrifugal time is 5-30 min.

[0016] In a second aspect, the present invention provides a nanosilver solution or a composite nanosilver solution obtained by the above method.

[0017] Based on the above technical solution, further, the particle size distribution of nanosilver in the nanosilver solution is between 10 and 40 nm, and the average particle size is 20 to 25 nm; the particle size distribution of composite nanosilver in the composite nanosilver solution is between 3 and 25 nm, and the average particle size is 8 to 15 nm.

[0018] In a third aspect, the present invention provides a method for preparing a nanosilver gel or a composite nanosilver gel, wherein the above-mentioned nanosilver solution or the composite nanosilver solution is uniformly mixed with 0.2-2wt% carbomer gel in an amount of equal weight to prepare the nanosilver gel or the composite nanosilver gel.

[0019] Based on the above technical scheme, further, the preparation process of the carbomer gel is: put the carbomer 2020 powder into purified water to expand, stir evenly to obtain 0.2-2wt% gel, add 0.2-2wt% triethanolamine, stir evenly, and obtain the carbomer gel.

[0020] In a fourth aspect, the present invention provides the above-mentioned preparation method to obtain nano silver gel or composite nano silver gel.

[0021] In a fifth aspect, the present invention provides the use of the above-mentioned nanosilver solution, composite nanosilver solution, nanosilver gel and composite nanosilver gel in the preparation of antibacterial materials, antiviral materials and wound and wound healing materials.

[0022] Based on the above technical solution, further, the nanosilver solution, composite nanosilver solution, nanosilver gel and composite nanosilver gel have multiple functions of high-efficiency antibacterial, antiviral, anti-inflammatory and promoting wound healing.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention utilizes an extract of oak leaves to prepare nano-silver or a nano-silver composite solution, and uses raw materials such as silver acetate to avoid the potential toxic side effects (the risk of nitrate radicals being converted into carcinogenic nitrosamines) of preparing nano-silver from silver nitrate. The preparation process is simple, the equipment investment is small, the cost is low, and no other chemical components need to be added during the reaction process. A large number of nano-silver particles can be prepared in a short time. The preparation process is pollution-free and does not contain any harmful chemical components. The nano-silver prepared from the extract of oak leaves is a green and environmentally friendly product, has high-efficiency and broad-spectrum antibacterial and antiviral properties, and has broad application prospects in the fields of pharmaceutical materials, medical and health care, and the like.

[0025] 2. The nanosilver solution prepared using oak leaf extract has highly effective and broad-spectrum antibacterial and antiviral properties, which provides an important experimental basis for the development of new antibacterial and antiviral preparations for skin and mucous membranes.

[0026] 3. The composite nanosilver gel prepared using oak leaf extract with pharmaceutical activity also contains silver, zinc and copper elements. It has the functions of highly efficient antibacterial and anti-inflammatory properties, improving tissue cell activity, and promoting rapid healing of wounds and wound surfaces. This has laid an important experimental foundation for the development of composite nanosilver medical research.

[0027] 4. The present invention expands the development and application field of oak leaves, expands the utilization scope and application value of oak resources, and utilizes the strong reducing properties of oak leaf extract to prepare a variety of metal nanoparticles. These metal nanoparticles have important application value in antibacterial, antiviral and wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.

[0029] Figure 1 This is a graph showing the test results of the nanosilver solution and the composite nanosilver solution prepared in Example 2 after being placed at room temperature for 3 months, wherein 1 is the nanosilver solution and 2 is the composite nanosilver solution.

[0030] Figure 2 This is a graph showing the particle size and distribution of the nanosilver solution prepared under ultrasonic conditions in Example 4.

[0031] Figure 3 Result diagram of particle size and distribution of the nanosilver solution prepared without ultrasound in Example 4.

[0032] Figure 4 This is the transmission electron microscopy detection result of the composite nanosilver solution in Example 5.

[0033] Figure 5 This is a graph showing the test results of the scanning transmission electron microscope energy spectrum analysis (STEM+EDS) of the composite nanosilver solution in Example 5.

[0034] Figure 6 This is a graph showing the results of the nanosilver inhibition zone test in Example 6, wherein A is Escherichia coli, B is Staphylococcus aureus, number 1 on the plate is a nanosilver solution, number 2 is a composite nanosilver solution, number 3 is a nanosilver gel, and number 4 is a composite nanosilver gel.

[0035] Figure 7 This is a graph showing the test results of the electron microscope observation of the adsorption and destruction of Staphylococcus aureus by the nanosilver solution in Example 6, wherein A is Staphylococcus aureus + nanosilver, and B is Staphylococcus aureus.

[0036] Figure 8This is a graph showing the test results of the electron microscope observation of the adsorption and destruction of Escherichia coli by the nanosilver solution in Example 6, wherein A is Escherichia coli + nanosilver, and B is Escherichia coli.

[0037] Fig. 9 This is a graph showing the test results of the composite nano-silver solution in Example 7 for the destructive effect on influenza virus, wherein A is influenza virus + composite nano-silver solution, and B is influenza virus.

[0038] Fig.10 This is a graph showing the test results of the destruction of adenovirus by the composite nanosilver solution in Example 7, wherein A is adenovirus + composite nanosilver solution, and B is adenovirus.

[0039] Fig.11 This is a graph showing the experimental results of the composite nanosilver gel in Example 8 on the healing effect of mouse wounds. DETAILED DESCRIPTION

[0040] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.

[0041] Example 1: Preparation method of oak leaf extract

[0042] After fully drying the fresh oak leaves, crush them at high speed for 30 minutes with a wall-breaking machine to make oak leaf fine powder. Use purified water to make a 1wt% solution, boil it on low heat for 30 minutes, and place it at 4°C for 12 hours. After filtering through double-layer filter paper, centrifuge at 3000rpm for 15 minutes, then take the supernatant and filter and sterilize it with a 0.22μm filter membrane to obtain an oak leaf extract. The oak leaf extract is rich in tannic acid, flavonoids, vitamin C and other compounds, and has a very strong antioxidant effect.

[0043] Example 2: Preparation of Nanosilver Solution and Composite Nanosilver Solution Using Oak Leaf Extract

[0044] (1) Preparation of nanosilver solution: 1000 ml of silver acetate solution containing 100 μg / ml of silver was prepared by mixing silver acetate with purified water. 20 ml of the oak leaf extract prepared in Example 1 was slowly added to the silver acetate solution at an ultrasonic frequency of 40 kHz and an ultrasonic power of 1080 W. The solution was stirred from time to time and the reduction reaction was continued for 15 minutes to prepare a nanosilver solution. The solution was placed at room temperature for 3 months without obvious precipitation. The results are shown in FIG. Figure 1 .

[0045] (2) Preparation of composite nano-silver solution: Silver acetate, copper acetate and zinc acetate were prepared into 1000 ml of a mixed solution containing 100 μg / ml of silver and 50 μg / ml of copper and zinc respectively with purified water. Under the conditions of ultrasonic frequency of 40 kHz and ultrasonic power of 1080 W, 20 ml of the oak leaf extract prepared in Example 1 was slowly added to the above solution, with occasional stirring. The reduction reaction was continued for 15 minutes to prepare a composite nano-silver solution. No obvious precipitation was observed after the solution was placed at room temperature for 3 months. Figure 1 .

[0046] Example 3: Preparation of Nanosilver Gel and Composite Nanosilver Gel Using Oak Leaf Extract

[0047] (1) Preparation of nanosilver gel: Silver acetate was prepared into 1000 ml of silver acetate solution containing 200 μg / ml silver with purified water. Under the conditions of ultrasonic frequency of 40 kHz and ultrasonic power of 1080 W, 20 ml of the oak leaf extract prepared in Example 1 was slowly added to the silver acetate solution, with occasional stirring. The reduction reaction was continued for 15 minutes to prepare a nanosilver solution. Then, the solution was fully mixed with an equal mass of 1% carbomer gel (10 g of carbomer 2020 powder was put into 1000 ml of purified water and swelled overnight. The next day, after stirring evenly, 10 g of triethanolamine was added and stirred evenly to prepare a gel) and stirred evenly to prepare a nanosilver gel.

[0048] (2) Preparation of composite nano silver gel: Silver acetate, copper acetate and zinc acetate were prepared into 1000 ml of a mixed solution containing 200 μg / ml of silver and 100 μg / ml of copper and zinc respectively with purified water. Under the conditions of ultrasonic frequency of 40 KHz and ultrasonic power of 1080 W, 20 ml of the oak leaf extract prepared in Example 1 was slowly added to the above solution, with stirring from time to time, and the reduction reaction continued for 15 minutes to prepare a composite nano silver solution. Then, the composite nano silver gel was prepared by fully mixing with 1% carbomer gel of equal weight and stirring evenly.

[0049] Example 4: Particle size detection of nanosilver solution

[0050] The nanosilver solution prepared in Example 2 (1) was tested for the size and distribution of nanosilver particles using a BeNano laser particle size analyzer; nanosilver prepared from oak leaf extract without ultrasound was used as a control group.

[0051] Under the condition of ultrasound, the particle size and distribution of nanosilver prepared from oak leaf extract are shown in Figure 2 The particle size is mainly distributed between 10 and 40 nm, with an average particle size of 22.43 nm. In the absence of ultrasound, the nanosilver prepared from the oak leaf extract showed two absorption peaks, and the particle size was mainly distributed between 20 and 120 nm, with an average particle size of 56.35 nm. Figure 3 .

[0052] Example 5: Transmission electron microscopy and scanning transmission electron microscopy energy spectrum analysis (STEM+EDS) of composite nanosilver solution

[0053] The composite nanosilver solution prepared in (2) of Example 2 was observed for nanoparticles using a transmission electron microscope. Figure 4 The particle size of the nanoparticles is distributed between 3 and 25 nm, with an average particle size of about 10 nm. The results of the scanning transmission electron microscope energy spectrum analysis are shown in Figure 5 The results showed that the composite nanosilver solution contained three types of particles: nanosilver, nanocopper and nanozinc. These nanoparticles were mainly round and the size of the nanoparticles ranged from 3 to 25 nm.

[0054] Example 6: Antibacterial effect of nanosilver prepared from oak leaf extract

[0055] (1) Inhibition zone test

[0056] The broth cultures of Escherichia coli and Staphylococcus aureus in logarithmic growth phase were diluted to 10 5 CFU / ml, 100 μL of each was evenly coated on the nutrient agar medium, and then a sterile punch was used to punch holes on the surface of the medium and the medium in the hole was picked out. The nanosilver solution, composite nanosilver solution, nanosilver gel and composite nanosilver gel prepared in Example 2 and Example 3 were added to each well, 80 microliters per well. The medium was then cultured at 37°C overnight, and the medium was taken out the next day to measure the diameter of the inhibition zone of each well.

[0057] The test results are shown in Figure 6 The results showed that the diameters of the inhibition zones of nanosilver solution and composite nanosilver solution against Escherichia coli were 10.0 mm and 11.0 mm, respectively; and the diameters of the inhibition zones against Staphylococcus aureus were 12.5 mm and 13.0 mm, respectively. The diameters of the inhibition zones of nanosilver gel and composite nanosilver gel against Escherichia coli were 8.0 mm and 8.5 mm, respectively; and the diameters of the inhibition zones against Staphylococcus aureus were 11.5 mm and 11.0 mm, respectively. The results of the inhibition zone experiment showed that the nanosilver solution, composite nanosilver solution, nanosilver gel and composite nanosilver gel prepared from oak leaf extract had significant inhibitory effects on Escherichia coli and Staphylococcus aureus.

[0058] (2) Electron microscopic observation of the adsorption and destruction of Escherichia coli and Staphylococcus aureus by nanosilver solution

[0059] Take the nano silver solution prepared in (1) of Example 2 and 10 5 Escherichia coli or Staphylococcus aureus at equal multiples of CFU / mL were mixed and allowed to react at 37°C for 1 hour before being examined by transmission electron microscopy.

[0060] The electron microscopy results are shown in Figure 7 and Figure 8 , Figure 7 The results showed that nanosilver has a strong adsorption capacity for Staphylococcus aureus. The nanoparticles adsorbed on the surface of the bacteria can cause the loss of activity of important enzymes on the surface of the bacteria, and the bacteria stop dividing and proliferating. Figure 8 The results showed that nanosilver particles also showed obvious adsorption effect on Escherichia coli. The surface structure of Escherichia coli treated with nanosilver was blurred, and obvious cracks formed on the surface of the bacteria, which was significantly different from the control bacteria. The surface structure of the control bacteria was clearly visible, and the pili structure was clear.

[0061] Example 7: Antiviral effect of composite nanosilver solution prepared from oak leaf extract

[0062] The composite nanosilver solution prepared in (2) of Example 2 was respectively mixed with the influenza virus (H3N2) solution (10 5 PFU / ml) and adenovirus solution (10 5 PFU / ml) were mixed in equal volumes and allowed to react at 37°C for 2 hours before being examined by transmission electron microscopy.

[0063] The transmission electron microscopy results are shown in Fig. 9 and Fig.10 The results showed that nanosilver caused the influenza virus and adenovirus to lyse and completely lose their original viral surface structure, which was significantly different from the control influenza virus and adenovirus.

[0064] Example 8: Effect of composite nanosilver gel on wound healing in mice

[0065] Five mice weighing 22-25 grams were anesthetized by intraperitoneal injection of 0.4 ml of 4% chloral hydrate. The hair on the back of the mice was shaved off, and a circular wound with a diameter of 15 mm was cut on the left and right skin of the back of the mice. The composite nano silver gel prepared in (2) of Example 3 was applied to the wound surface on the right side of the back of the mice (nano silver content 100 μg / ml, nano copper and nano zinc were 50 μg / ml each). The wound on the left side of the back was used as a control and silver ion gel (silver ion content 100 μg / ml) was applied. The wound was applied twice a day for 1 week, and the healing of the wounds on the left and right sides of the back of the mice was observed. The healing area of ​​the wound was calculated, and the wound healing rate was calculated by comparing it with the wound area of ​​the initial position.

[0066] The test results are shown in Fig.11 The results showed that the wound healing rate of mice in the experimental group was 64.8%, while that of mice in the control group was only 43.3%. There was a significant difference between the two groups, with a p value of less than 0.05.

[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing nanosilver or composite nanosilver based on oak leaf extract, characterized in that: The method comprises the following steps: mixing an oak leaf extract with a silver salt solution or a composite solution of silver salt, copper salt and zinc salt, and performing a reduction reaction under ultrasonic action to prepare a stable nano silver solution or a composite nano silver solution; the volume ratio of the oak leaf extract to the silver salt solution or the composite solution of silver salt, copper salt and zinc salt is 1000:1-100:5; the silver ion concentration in the silver salt solution is 50-1000 μg / ml; the silver ion concentration in the composite solution of silver salt, copper salt and zinc salt is 50-1000 μg / ml, the copper ion concentration is 25-500 μg / ml, and the zinc ion concentration is 25-500 μg / ml; and the reduction reaction time is 10-60 minutes.

2. The method according to claim 1, characterized in that The silver ion concentration in the silver salt solution is 50-200 μg / ml; the silver ion concentration in the composite solution of silver salt, copper salt and zinc salt is 50-200 μg / ml, the copper ion concentration is 25-100 μg / ml, and the zinc ion concentration is 25-100 μg / ml; the silver salt is silver acetate, the copper salt is copper acetate, and the zinc salt is zinc acetate.

3. The method according to claim 1, characterized in that The ultrasonic conditions are as follows: ultrasonic frequency of 25-80KHz and ultrasonic power of 54-1080W.

4. The method according to claim 1, characterized in that: The preparation process of the oak leaf extract is as follows: crushing the dried oak leaves, adding purified water to the obtained oak leaf dry powder to form a 0.1wt% to 5wt% solution, extracting at 80 to 100°C for 15 to 60 minutes, then placing at 1 to 4°C for 10 to 24 hours, filtering and centrifuging, taking the supernatant, and filtering and sterilizing with a filter membrane to obtain the extract.

5. The method according to claim 4, characterized in that The content of oak leaf dry powder in the solution is 0.5wt%-2wt%; the centrifugal conditions are: the rotation speed is 2000-5000rpm, and the centrifugal time is 5-30min.

6. The nano silver solution or composite nano silver solution obtained by the method according to any one of claims 1 to 5.

7. The nano silver solution or composite nano silver solution according to claim 6, characterized in that: The particle size of the nanosilver in the nanosilver solution is distributed between 10 and 40 nm, and the average particle size is 20 to 25 nm; the particle size of the composite nanosilver in the composite nanosilver solution is distributed between 3 and 25 nm, and the average particle size is 8 to 15 nm.

8. A method for preparing nano silver gel or composite nano silver gel, characterized in that: The nano silver solution or composite nano silver solution according to claim 6 or 7 is mixed evenly with 0.2-2 wt % carbomer gel in equal times of mass to prepare the nano silver gel or composite nano silver gel.

9. The preparation method according to claim 8 obtains nano silver gel or composite nano silver gel.

10. Use of the nanosilver solution or composite nanosilver solution according to claim 6 or 7, and the nanosilver gel or composite nanosilver gel according to claim 9 in the preparation of antibacterial materials, antiviral materials and wound and wound healing materials.

Citation Information

Patent Citations

  • Method for preparing silver nano granules by reducing plant extract

    CN101912976A

  • Method for preparing nano silver particles by using plant extract for reduction, and application of method

    CN102240815A

  • Preparation method of even and stable nano-silver water solution

    CN102941354A

  • Method of biosynthesis of nano-silver by utilizing extract of Guangxi vittex cannabi folia leaves

    CN106862590A

  • Method for preparing nano-silver based on kapok extracting solution

    CN114734032A